Pengaruh Ukuran Perusahaan, Profitabilitas, Dan Leverage Terhadap Corporate Social Responcibility - Bustanul Ulum (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2023)
Objective : This study aims to determine and analyze the effect of Company Size, Profitability and Leverage on Corporate Social Responsibility in Food and Beverages companies listed on the Indonesia Stock Exchange (IDX) during the period 2016 – 2020. The results of this study are expected to be used by companies as material evaluation in order to increase the disclosure of Corporate Social Responsibility. Research method : This study uses a quantitative approach. The method used is the method of multiple linear regression analysis, by testing classical assumptions, testing hypotheses and coefficients of determination. The population of this study were 30 food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the period 2016 – 2020. Based on the purposive sampling method, a sample of 11 companies was obtained. The data analysis technique used in this research is multiple linear regression. Findings : The results obtained partially, Firm Size has a significant effect on Corporate Social Responsibility, Profitability has a significant effect on Corporate Social Responsibility, and Leverage has no and no significant effect on Corporate Social Responsibility. Meanwhile, simultaneously, Company Size, Profitability, and Leverage have a significant effect on Corporate Social Responsibility.